Assessment of the quality of groundwater sources in Sitio Gines-Tacas, Brgy. Palaca, Miag-ao, Iloilo - Divinagracia, Sheila Marie Suanque
The quality of selected groundwater sources in Sitio Gines-Tacas Brgy. Palaca, Miag-ao, Iloilo was assessed.